2019
DOI: 10.1246/bcsj.20190014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible-Light-Driven H2 Production via UiO-66 Nanospheres Attached to Flower-Shaped ZnIn2S4 Microspheres

Abstract: Photocatalytic hydrogen production is an effective strategy for meeting energy challenges. Here, a composite for photocatalytic hydrogen production via introduction of UiO-66 nanospheres into flower-shaped ZnIn2S4 microspheres (ZIS/U6) is described. The optimum composite with 20 mg UiO-66 loading displayed the high photocatalytic rate of 1860.9 µmol g−1 h−1 with an apparent quantum efficiency of 1.4% at 420 nm under visible-light irradiation, which is nearly 3 times higher than that of ZnIn2S4. The improved ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Firstly, when the UPC photocatalyst is excited by absorbing photons from the irradiation, the photo-generated electrons and holes are generated in CNNS and organic ligands of UiO-66, as reported in previous studies. 7,34,35 On the one hand, the photo-generated electrons migrate from VB ( E vb = 1.99 V) to CB ( E cb = −0.92 V) of CNNS, and then transfer to the CB (−0.55 V) of UiO-66 through the conductive PDA layer. This can be further confirmed by the electron lifetime of UPC (8.1 ns) being superior among those of UC (7.4 ns), UiO-66 (6.9 ns) and CNNS (3.3 ns); on the other hand, the electrons can also transfer from VB ( E vb = 3.46 V) to CB ( E cb = −0.55 V) of UiO-66.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, when the UPC photocatalyst is excited by absorbing photons from the irradiation, the photo-generated electrons and holes are generated in CNNS and organic ligands of UiO-66, as reported in previous studies. 7,34,35 On the one hand, the photo-generated electrons migrate from VB ( E vb = 1.99 V) to CB ( E cb = −0.92 V) of CNNS, and then transfer to the CB (−0.55 V) of UiO-66 through the conductive PDA layer. This can be further confirmed by the electron lifetime of UPC (8.1 ns) being superior among those of UC (7.4 ns), UiO-66 (6.9 ns) and CNNS (3.3 ns); on the other hand, the electrons can also transfer from VB ( E vb = 3.46 V) to CB ( E cb = −0.55 V) of UiO-66.…”
Section: Resultsmentioning
confidence: 99%
“…4c), suggesting the excellent photocatalytic hydrogen-evol- ution performance of UEDNiS/ZIS. 10,[28][29][30][31][32][33][34] The cyclic stability of the catalyst in photocatalytic hydrogen-production tests over UEDNiS/ZIS was investigated. As displayed in Fig.…”
Section: Photocatalytic H 2 -Generation Performancementioning
confidence: 99%
“…[26] Different polymorphs of ZIS have different applications. Many studies have revealed that the hexagonal ZIS and the cubic-phase ZIS have excellent photocatalytic activity under visible [27][28][29] and NIR light [30,31] irradiation and exhibit considerable chemical stability. For example, the hexagonal ZIS flower-like microspheres doped with black phosphorus quantum dots (QDs) prepared by Pan et al have excellent photocatalytic hydrogen evolution activity.…”
Section: Crystal Structures Optical Propertiesmentioning
confidence: 99%
“…The synthesis of MOF-derived materials requires an organic solvent environment. This excellent composite material composed of ZIS and MOFs, such as UiO-66, [28,94,95] UiO-66-(COOH) 2 , [96] NH 2 -UiO-66, [97] MIL-125(Ti), [98] and NH 2 -MIL-125(Ti), [99,100] has been prepared through the solvothermal method. For example, Peng et al prepared the novel nanostructured UiO-66@ZIS photocatalysts by coating ZIS nanosheets on UiO-66 nanospheres by a simple solvothermal method, and the samples synthesized by this method had uniform structures and improved photocatalytic activity for hydrogen production under visible light illumination, as shown in Figure 9.…”
Section: Zis-based Compositesmentioning
confidence: 99%